Natural Frequency Analysis of a Parallel Legged Walking Robot with Clearance - Chengzhi Su; Jian Sun; Jinghua Wang; Daoxue Liu; Mingying Chen; Fangyuan Han (Jixie chuandong)
Aiming at the phenomenon of vibration and abnormal joint response in the operation of walking robot，the dynamics method is adopted to simulate the contact state of the clearance model of the moving pair，and the natural frequency of the walking robot with clearance is analyzed，avoiding the problem that the nonlinear factors are ignored in the simulation analysis of the computational modal analysis method. With the help of transient dynamics simulation，the displacement response of the walking robot with clearance is calculated，and then through the Fourier transform，the frequency response curve is obtained，the corresponding frequency of the curve peak is the natural frequency of the walking robot with clearance. The existence of joint clearance can reduce the natural frequencies of the walking robot，but the clearance does not affect the mode shapes. The first-order mode is the sway vibration of the platform and the support leg along the X-axis，the second-order mode is orthogonal to the first-order mode，and the third-order mode is the torsional vibration of the platform and the support leg along the Z-axis.